(3eMOOGJ GdJMXjQ GdfaSj GdQjGVj dOi dGYHj GdefJNH GdhWfj GdLRGFQj dcQI GdbOe (B: (3OQGSI hUajI JMdjdjI dhLgGJ fXQGdeNJUjf h GdJbfjjf Mhd GfYcGS GdJMVjQ GdfaSj Ydi GOGA dGYHj GdefJNH GdhWfj GdLRGFQj dcQI GdbOe ddaJQI eG Hjf (B2018 - 2023 s - (3Hf SGde Jhajb, s; (3jhSaj, aJMjs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2023)
(3jYJHQ GdJMVjQ GdfaSj GdQjGVj ef Cge YhGed GdfLGM aj GdeeGQSI GdQjGVjI HUaI YGeI, MjK JJhba GdcKjQ ef GdfJGFL GdeMbbI ef WQa GdQjGVjf aj eNJda GdefGaSGJ hGdJXGgQGJ GdQjGVjI Ydi eOi GdJMVjQ hGdGSJYOGO GdfaSj, hcKjQG eG jNab GdQjGVjhf hGdefJNHGJ hGdaQb aj JMbjb GdfJGFL GdeQLhI HSHH JaGUjd dG jJe JMOjOgG HTcd Objb, ajZjH GdJaSjQ GdYdej hGdQjGVj dCSHGH GdaTd, hNdGd GdSfhGJ GdCNjQI, hef NdGd eJGHYI fJGFL heHGQjGJ GdefJNH GdhWfj dcQI GdbOe QLGd, dhMX Cf COGA GdefJNH GdhWfj aj cKjQ ef GdaJQGJ YQa JMSfG cHjQG, aj Mjf jJSGAd GdcKjQ Mhd CSHGH GdENaGb aj HYV GdeHGQjGJ GdeUjQjI, heG GdCSHGH GdJj cGfJ hQGA Pdc, hdCLd Gdhbha Ydi eOi GdJMVjQ GdfaSj GdQjGVj ddGYHj GdefJNH GdQjGVj heG EPG cGfJ gfGc YdGbI Hjf eG jMbbg GdefJNH GdhWfj ef fJGFL heG jbOeg ef COGA eQJHW HGdJMVjQ GdfaSj Ce dG, MGhdfG aj OQGSJfG gPg Cf fSJWdY QCj GdeNJUjf hGdJbfjjf hGdQjGVjjf hGdeOQHjf hcd ef dg YdGbI HeeGQSI cQI GdbOe ef GdfGMjI GdJbfjI hGdYedjI Mhd GdeMOOGJ GdfaSjI ddGYHj GdefJNH GdhWfj dcQI GdbOe, heOi YdGbJgG hGQJHGWgG HGdCOGA GdYGe ddefJNH GdhWfj, hPdc ef NdGd OQGSI hUajI JMdjdjI dBQGA YjfI ef GdaFGJ GdJj PcQfGg, eQhQG HeLehYI ef GdNWhGJ GdefgLjI hGdfXQjI hGdYedjI hGdJWHjbjI, hJhUdfG Edi LedI ef GdfJGFL GdJj JVefJgG gPg GdOQGSI ef NdGd NeSI aUhd Hjf GdfXQj hGdJWHjbj, acGfJ GdETcGdjI GdYGeI ddOQGSI(B: (3cja jfXQ GdeNJUjf hGdJbfjf aj cQI GdbOe Edi GfYcGSGJ GdJMVjQ GdfaSj Ydi COGA dGYHj GdefJNH GdhWfj GdLRGFQj dcQI GdbOe?(B. (3GdcdeGJ GdeaJGMjI(B: (3GdefJNH GdhWfj GdLRGFQj, cQI GdbOe, GdJMVjQ GdfaSj GdQjGVj, GdeMOOGJ GdfaSjI(B. s
(3OcJhQGIs
Keywords: (3GdJMVjQ GdfaSj s; (3GdJMVjQ GdfaSj GdQjGVj s; (3cQI GdbOes